CONTENT-PROCESS APPROACH IN PROJECTING PROFESSIONALISM OF A MODERN TEACHER (Pedagogy of Higher and Secondary Education, 2010)
The article reveals the essence, the main haracteristics of content-proceural approach in learning and its possibilities in the professional formation of futre teachers in university education.
Keywords: knowledge approach to the educational process; content-proceural approach of education; content-proceural model of education; the structural components in the cognitive activity